Integrated Waste Management Place and Environmental Pillar Sustainable Development Goals: Solution or Threat? - Gde Putra Mahendra Junior; I Nyoman Bagiastra; Kadek Julia Mahadewi (West Science Interdisciplinary Studies, 2024)
This article discusses the issue of the Kesiman Kertalangu Integrated Waste Management Site (TPST) which has an impact on the surrounding community because the smoke produced causes disruption to people's sense of smell and even threatens public health, but basically the community is not protesting regarding the existence of the TPST but rather the impact caused by its activities. This article uses a normative legal research method, by taking a statutory approach, then the data collected will be processed using a qualitative approach and explained descriptively. The Kesiman Kertalangu TPST violates the right to a clean and healthy environment as mandated by the constitution, UUPPLH and the Sustainable Development Goal's concept. It is hoped that the government's responsibility regarding the impacts that occur will refer to article 54 UUPPLH and 82 of the Job Creation Law, then the Kertalangu TPST must have an SDG concept, especially Village SDGs, guided by Village SDG number 3, environmental restoration efforts must be made based on UUPPLH and the Job Creation Law. and carrying out sustainable waste management based on SDG's principles as well as developing technology is very necessary in solving problems by comparing it with waste management in Singapore, namely processing smoke from combustion into electrical power and scarp metal which produces high economic value.